1973
DOI: 10.1042/cs0450633
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Metabolism of Human Insulin and Porcine Proinsulin in Man

Abstract: 1. The metabolism of unlabelled monocomponent human insulin and porcine proinsulin was studied in ten normal subjects (five males and five females) by using a priming dose-constant-infusion technique. In each subject, the metabolic clearance rate (MCR) was measured at four separate steady-state hormone concentrations averaging 16-21 6 punitslml (insulin) and 4-2-42.8 ng/ml (proinsulin).2. For insulin the MCR fell progressively from 34 ml kg-' min-' at a mean fasting insulin concentration of 3.8 punitslml to 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
90
4

Year Published

1981
1981
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 34 publications
16
90
4
Order By: Relevance
“…Alternatively, if insulin is given at a high rate of infusion, pancreatic secretion is suppressed and can be considered to be negligible. These techniques have been used in the demonstration that insulin clearance decreases with insulin concentration [23][24][25]. Under nonsteady-state conditions on the other hand, the value of k (or MCR) can be…”
Section: The Measurement Of the Mcr Of Glucosementioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, if insulin is given at a high rate of infusion, pancreatic secretion is suppressed and can be considered to be negligible. These techniques have been used in the demonstration that insulin clearance decreases with insulin concentration [23][24][25]. Under nonsteady-state conditions on the other hand, the value of k (or MCR) can be…”
Section: The Measurement Of the Mcr Of Glucosementioning
confidence: 99%
“…We can therefore establish the proportion for the part of MCR which is related to insulin action. /3=mi (24) where m is a constant and i is the plasma concentration of insulin. From Eq.…”
Section: The Relationships Of Mcr To Insulin and Glucosementioning
confidence: 99%
“…Thus, the over-all disappearance of the initial phase, evaluated on the basis of clinical study, was used to calculate the post-hepatic insulin delivery rate. To avoid any potential effect of hypoglycaemia on insulin disappearance [11][12][13][14], glucose was also administered intravenously. Constantly infused glucose used in our procedure has been reported to reduce markedly hepatic glucose output without a concomitant increase in total glucose utilization [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of the disappearance rate of unlabelled insulin may be complicated by the fact that plasma glucose concentration is decreased. The influence of hypoglycaemia on the disappearance rate of insulin, however, is generally considered insignificant [11][12][13][14], even if endogenous insulin is unchanged or suppressed. It has been reported that the absolute degradation rate of insulin is proportional to the plasma insulin concentration, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation